PENGARUH SERVICESCAPE TERHADAP MINAT KUNJUNG (STUDI KASUS CAFÉ DOPAMINE RINGROAD MEDAN) - Idahwati; Simanjuntak, Owen De Pinto; Pasaribu, Eva Solita; Hulu, Feberman (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This research was designed to explore and examine in depth how elements in the servicescape can influence visitor interest. This study adopted a quantitative descriptive approach. Research subjects included a total of 20,400 individuals, which represents the number of visitors from January to August 2024. From this population, 100 respondents were randomly selected using the Random Sampling method. To analyze the data, this research applied a series of statistical tests, including Instrument Test, Classic Assumption Test, Simple Linear Regression, Hypothesis Test, and Coefficient of Determination Test (R²). The results of the partial test (t test) indicate that servicescape has a significant and positive influence on visiting interest. Meanwhile, the results of the coefficient of determination (R²) test show that servicescape contributes 73.30% to the variable interest in visiting, while the remaining 26.70% is influenced by other factors not examined in this study.